The clinical effectiveness of cognitive behaviour therapy for chronic insomnia: implementation and evaluation of a sleep clinic in general medical practice. - Espie, C; Inglis, S; Tessier, S; Harvey, L (2001)
Chronic insomnia is a very common clinical condition which may respond well to non-pharmacological treatment. Indeed, the literature supports the efficacy of cognitive behaviour therapy (CBT). However, there has been no substantial study of clinical effectiveness. Since insomniacs typically present in general medical practice this is a crucial gap in the outcome research. This study, therefore, specifically investigated the clinical effectiveness of CBT delivered by Health Visitors (primary care nurses) trained as therapists. One hundred and thirty-nine insomniacs (mean age 51 yr) were randomised to CBT or Self-Monitoring Control (SMC) in a controlled trial. CBT comprised six group sessions (n=4 to 6 patients). After the controlled phase, SMC patients entered deferred treatment (CBT-DEF), allowing both treatment replication and long-term outcome to be investigated for a sizeable, treated sample. Repeated measures ANOVAs demonstrated superiority of CBT over SMC in substantially reducing sleep latency and wakefulness during the night. CBT-DEF replicated similar effects and maintained improvement was observed in both groups one year later. Furthermore, total sleep increased significantly during follow-up and 84% of patients initially using hypnotics remained drug-free. Results suggest that CBT administered by Health Visitors offers a clinically effective treatment for insomnia.